Elastic Superhydrophobic and Photocatalytic Active Films Used as Blood Repellent Dressing. Issue 11 (3rd February 2020) - Liu, Jie; Ye, Lijun; Sun, Yuling; Hu, Minghan; Chen, Fei; Wegner, Seraphine; Mailänder, Volker; Steffen, Werner; Kappl, Michael; Butt, Hans‐Jürgen
Abstract: Durable and biocompatible superhydrophobic surfaces are of significant potential use in biomedical applications. Here, a nonfluorinated, elastic, superhydrophobic film that can be used for medical wound dressings to enhance their hemostasis function is introduced. The film is formed by titanium dioxide nanoparticles, which are chemically crosslinked in a poly(dimethylsiloxane) (PDMS) matrix. The PDMS crosslinks result in large strain elasticity of the film, so that it conforms to deformations of the substrate. The photocatalytic activity of the titanium dioxide provides surfaces with both self‐cleaning and antibacterial properties. Facile coating of conventional wound dressings is demonstrated with this composite film and then resulting improvement for hemostasis. High gas permeability and water repellency of the film will provide additional benefit for medical applications. Abstract : A nonfluorinated, elastic, superhydrophobic film is reported, to be used as medical wound dressings to enhance their hemostasis function. The photocatalytic activity of the titanium dioxide nanoparticles included provides surfaces with self‐cleaning and antibacterial properties. Through facile coating of conventional wound dressings with this composite film, an effective hemostasis is demonstrated.